Is There an Output Free Lunch for Fiscal Inationary Policies? - Moises S. Andrade; Tiago Berriel (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2016)
Expansionary fiscal policies have been advocated to induce output expansions and inflation in deep recession or deflationary episodes. We show that, in a fiscalist setup, an increase in deficits can trigger a stagflation by negatively affecting financial intermediation of resources to investments. Financial intermediaries collect deposits to buy government bonds and lend through nominal long-term loans. When intermediaries face financial frictions and a maturity mismatch on their assets and liabilities, a surprise inflation and/or a revaluation of bonds prices impair their net-worth reducing lending, investments, and output. Recession comes with in- flation in a fiscal expansion because the fall on capital triggered on the financial sector rises production firms marginal costs. The probability of a recession is higher the greater is the maturity mismatch, the sensitivity of bonds prices to the policy rate, and the share of bonds on banks balances. These results: (1) give theoretical support for the negative relation documented between financial sector performance and inflation (2) help explaining high debt, high inflation environments coinciding with banking crisis and, more importantly, (3) expose drawbacks of fiscal inflation policies proposed to inflate and stimulate low inflation economies, where the setup stressed in this paper is more probable to be present.
Keywords: 330